Impact of Actuarial Valuation Methods on Pension Fund Liabilities in Kenya - Mbatia, John (American Journal of Statistics and Actuarial Sciences, 2024)
Purpose: The aim of the study was to assess the impact of actuarial valuation methods on pension fund liabilities in Kenya. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study indicated that the choice of actuarial method can lead to considerable differences in the calculated liabilities, influencing the required contributions and the overall funding status of pension plans. For instance, the PUC method, which considers future salary increases and length of service, typically results in higher liability estimates compared to the EAN method, which spreads the cost of benefits evenly over an employee’s career. The Aggregate method, on the other hand, combines aspects of both, potentially smoothing out contribution requirements over time. The findings highlight that the actuarial assumptions underpinning these methods, such as discount rates, mortality rates, and salary growth, further amplify the variability in liability estimates. Consequently, the selection of an appropriate actuarial valuation method, aligned with the specific characteristics and funding objectives of the pension plan, is critical for accurate liability measurement and effective financial management. Implications to Theory, Practice and Policy: Modern portfolio theory (MPT), agency theory and life-cycle hypothesis may be used to anchor future studies on assessing the impact of actuarial valuation methods on pension fund liabilities in Kenya. Pension funds should establish protocols for the regular review and adjustment of actuarial assumptions, such as discount rates and salary growth rates, to reflect current economic conditions and demographic trends accurately. Policymakers should develop and enforce regulatory frameworks that mandate the use of robust and adaptive actuarial valuation methods across public and private pension funds.